A systematic review of interventions to increase breast and cervical cancer screening uptake among Asian women - Lu Mingshan; Moritz Sabina; Lorenzetti Diane; Sykes Lindsay; Straus Sharon; Quan Hude (BMC, 2012)
Abstract Background The Asian population is one of the fastest growing ethnic minority groups in western countries. However, cancer screening uptake is consistently lower in this group than in the native-born populations. As a first step towards developing an effective cancer screening intervention program targeting Asian women, we conducted a comprehensive systematic review, without geographic, language or date limitations, to update current knowledge on the effectiveness of existing intervention strategies to enhance breast and cervical screening uptake in Asian women. Methods This study systematically reviewed studies published as of January 2010 to synthesize knowledge about effectiveness of cancer screening interventions targeting Asian women. Fifteen multidisciplinary peer-reviewed and grey literature databases were searched to identify relevant studies. Results The results of our systematic review were reported in accordance with the PRISMA Statement. Of 37 selected intervention studies, only 18 studies included valid outcome measures (i.e. self-reported or recorded receipt of mammograms or Pap smear). 11 of the 18 intervention studies with valid outcome measures used multiple intervention strategies to target individuals in a specific Asian ethnic group. This observed pattern of intervention design supports the hypothesis that employing a combination of multiple strategies is more likely to be successful than single interventions. The effectiveness of community-based or workplace-based group education programs increases when additional supports, such as assistance in scheduling/attending screening and mobile screening services are provided. Combining cultural awareness training for health care professionals with outreach workers who can help healthcare professionals overcome language and cultural barriers is likely to improve cancer screening uptake. Media campaigns and mailed culturally sensitive print materials alone may be ineffective in increasing screening uptake. Intervention effectiveness appears to vary with ethnic population, methods of program delivery, and study setting. Conclusions Despite some limitations, our review has demonstrated that the effectiveness of existing interventions to promote breast and cervical cancer screening uptake in Asian women may hinge on a variety of factors, such as type of intervention and study population characteristics. While some studies demonstrated the effectiveness of certain intervention programs, the cost effectiveness and long-term sustainability of these programs remain questionable. When adopting an intervention program, it is important to consider the impacts of social-and cultural factors specific to the Asian population on cancer screening uptake. Future research is needed to develop new interventions and tools, and adopt vigorous study design and evaluation methodologies to increase cancer screening among Asian women to promote population health and health equity.